Liquid First Is “Solid” in Naïve Non-Small Cell Lung Cancer Patients: Faster Turnaround Time With High Concordance to Solid Next-Generation Sequencing - Sehayek, Or; Kian, Waleed; Onn, Amir; Stoff, Ronen; Sorotsky, Hadas Gantz; Zemel, Melanie; Bar, Jair; Dudnik, Yulia; Nechushtan, Hovav; Rottenberg, Yakir; Soussan-Gutman, Lior; Dvir, Addie; et al. (Frontiers in Oncology, 2022)
Purpose Molecular profiling is crucial in naïve non-small cell lung cancer (NSCLC). While tissue-based analysis is challenged by turnaround time and scarcity of tissue, there is increasing demand for liquid biopsy. We aimed to analyze the use of upfront liquid biopsy as a molecular profiling approach. Methods This retrospective multicenter, non-interventional study compared findings and turnaround times of liquid vs. standard-of-care (SOC) tissue-biopsy molecular profiling. The study included naïve advanced NSCLC patients with available liquid biopsy (Guardant360 CDx). Results A total of 42 consecutive patients (60% men; median age, 69.5 [39–87] years; 86% stage IV NSCLC) were identified between September 2017 and December 2020. Liquid-biopsy analysis provided results for all 42 patients, whereas the tissue-based analysis failed in 5 (12%) patients due to insufficient tumor samples. In 17 patients, 18 actionable driver mutations were identified. Eleven mutations were detected by both approaches (i.e., concordance of 61%), 4 only by liquid biopsy and 3 only by tissue biopsy. The median time from the molecular request to receiving the molecular solid report on the last biomarker was 21 (range: 5–66) days, whereas the median time from blood draw to the liquid-biopsy results was 10.5 (7–19) days. The median time between the availability of liquid-biopsy findings and that of the last biomarker was 5 days. Treatment changes following the liquid-biopsy results were observed in 3 (7%) patients. Conclusion Performing liquid-biopsy upfront is feasible and accurate and allows a shorter time for treatment in NSCLC, especially when tumor tissue is scarce.